“I didn't know anything, but I learned over time”: The process of nurses attaining autonomy in Intensive Care Units - Naranjo, Nestor; Florez, Inna; Gómez, Edna (Investigación y Educación en Enfermería, 2024)
Objective. Understand the social processes experienced by nursing professionals and the meanings underlying autonomy in adult Intensive Care Units in the city of Cartagena (Colombia). Methods. A qualitative study with a grounded theory approach was conducted. Fifteen semi-structured interviews were carried out with nursing professionals, and the analysis was based on the coding technique proposed by Strauss & Corbin. Results. Of the respondents, fourteen were female and one was male, with ages ranging from 23 to 57 years. Experience in intensive care units ranged from 1 to 28 years, and none had postgraduate studies. After thematic analysis, the central category was obtained from four categories: adaptation process, applicability of autonomy exercise, building autonomous competence, and limitations to the exercise of autonomy. Conclusion. Nursing professionals achieve their autonomy through a social process, based on different stages of learning when facing the environment of the units. It is grounded in decision-making and the power to act freely. However, barriers continue to hinder it, including limitations imposed by institutions, protocol-based interventions, social status, and individual differences among professionals